Pembuatan Bibliografi Beranotasi Khusus Terbitan Pemerintah Kabupaten Padang Pariaman di Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat - Putri, Dianne; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2016)
This paper discusses the Annotated Bibliography Making Special Issue Government in the Library and Archives of West Sumatra Province. This study aims to help users and librarians in making information retrieval using a means of controlling the form of a bibliography. Interest authors describe the manufacture khususi annotated bibliography Government Publications in the Library and Archives of West Sumatra Province. Writing this paper uses descriptive method. Data obtained from the collection directly, which is looking for the physical form in the library collection. The object of research is a special issue of the Government in the form of books as many as 70 titles. Based on data analysis, summarized things as follows: (1) the determination of title to consider the following matters: (a) tersediannya special collection of government publications, (b) the need for the library collection by pemustaka, (c) the need for documentation that includes the collection, processing and storage of information on a particular field of study. (2) the collection of library materials or information retrieval, (3) the selection of library materials, (4) grouping or calcification, (5) the keyword generation, (6) index, (7) typing the manuscript bibliography by using the writing APA (American Psycology Association, and the stage (8) manufacture bibliography is an examination of the final document which include inspection posts of errors in spelling and punctuation, suitability shortening and reversal of the author's name, writing in italics for the words of latin and magazine titles, completeness articles are used as material bibliography, index conformity with the referenced entry number, checking the layout of each piece of writing.Â Keyword: annotated bibliography, government publications, libraries